Flexural strength of bidirectional hybrid epoxy composites reinforced by E glass and T700S carbon fibres - Dong, Jonathan; Davies, I. (Elsevier Ltd, 2015)
A study on the flexural properties of bidirectional hybrid epoxy composites reinforced by E glass and T700S carbon fibres in inter-ply configurations is presented in this paper. Test specimens are made by hand lay-up and their flexural properties are obtained by three point bend test in accordance with ASTM D790-07. For comparison, the flexural behaviour is also modelled numerically using finite element analysis (FEA), and analytically using the Classic Lamination Theory (CLT). It is shown from the results that in general, good agreement is found between the experimental data and the model predictions. The flexural strength decreases when partial laminas from a carbon/epoxy laminate are replaced by glass/epoxy laminas. No significant hybrid effects for the flexural strength are found from the experiments. However, simulation studies show that hybridisation can potentially improve the flexural strength.